Fenomenologi Pelaku Usaha Sari Bumi sebagai Entrepreneur Muslim dalam Membangun Koneksi dan Komunitas Bisnis - Ana Aziza (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2019)
In Indonesia, the entrepreneurial culture is quite low. This can be seen from the very high interest of job seekers, high rates of poverty and unemployment. From the above phenomenon, the role of Muslims as the majority is needed to encourage the growth of the entrepreneurial spirit. This study seeks to portray the role of Sari Bumi entrepreneurs in building connections and business communities, using a phenomenological approach, researchers seek to explore what roles Sari Bumi entrepreneurs have played in building connections and business communities. Based on the results of the study, there have been 158 building material shops in Sidoarjo Regency which have been owned by 80 families. Based on data analysis in qualitative research, it was found 9 (nine) roles of Sari Bumi entrepreneurs in building a business community which include, opening up employment opportunities, building independence, encouraging the emergence of an entrepreneurial spirit, providing capital assistance, being an example in discipline, commitment to maintaining Islamic values, forming a forum for friendship, forming a foundation that is active in the social, educational and religious fields and establishing a distributor company.